Moisture adsorption and retention capacity of enzymatic hydrolysates from royal jelly under different humidity circumstances - LI Ying-hua; HU Fu-liang (浙江大学学报. 农业与生命科学版)
In order to research the moisture adsorption and retention capacity of enzymatic hydrolysates from royal jelly under different humidity conditions, the royal jelly proteins were hydrolyzed by alkali protease, and the moisture adsorption and retention capacity of their hydrolysates were determined under the conditions of 25 ℃, relative humidities of 20%, 50% and 65%, respectively, in comparison with lyophilized royal jelly powder and bone collagen. The results showed that the enzymatic hydrolysates exhibited better performance both in moisture adsorption and retention test than lyophilized royal jelly powder and bone collagen did. The optimum conditions were as follows: substrate concentration of 8%, enzymatic concentration of 1%, temperature of 45 ℃, enzymatic hydrolysis time of 3 h and pH 9.5. It is safe to draw the conclusion that enzymatic hydrolysis will be an efficient method for obtaining ingredients from royal jelly with good moisture adsorption and retention capacity and it has a bright future in exploitation of moisture-keeping or moisture-adsorbing cosmetic.